Internal friction due to long-range diffusion of hydrogen in the Nb-46 wt.% Ti alloy - Grandini, Carlos Roberto [UNESP]; Florêncio, Odila; Jordão, José Alberto Rodrigues (ABM, ABC, ABPol, 2003)
The Gorsky Effect was investigated by internal friction measurements in the Nb-46 wt.% Ti-H system. The internal friction measurements were performed in a torsion pendulum with frequency of 3.8 Hz in a temperature range from 80 to 700 K. An interpretation of the experimental data showed that the hydrogen diffusion coefficient D obeys the Arrhenius' law in the temperature interval of 300 to 700 K, with D0 = 7.4 × 10-4 cm²/s and activation energy E = (0.102 ± 0.005) eV. At low temperatures, Do and E were found to be respectively 2.0 × 10-4 cm²/s and (0.063 ± 0.005) eV, with a deviation of the Arrhenius law of higher temperatures.
Keywords: alloys; anelasticity; diffusion; mechanical properties